Differentiated Approach to Antibiotic Therapy for Acute Tonsillopharyngitis in Children - Ye.I. Yulish; O.Ye. Chernyshova; B.I. Krivuschev; A.K. Talalayenko (Zaslavsky O.Yu., 2014)
There has been considered an etiotropic differentiated approach to the administration of antibiotics for sore throat in children: in acute streptococcal tonsillopharyngitis drugs of choice are aminopenicillins, in allergy or resistance to them, as well as in cases of intracellular pathogens - Chlamydophila pneumoniae or Mycoplasma pneumoniae detection macrolides should be administered.